2019
DOI: 10.1109/jeds.2019.2933848
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Electrical Characteristics of ZnSnO/Si Bilayer Tunneling Filed-Effect Transistors

Abstract: We demonstrate improvement of electrical characteristics of a bilayer tunneling field effect transistor (TFET) composed of an n-type zinc-tin-oxide (ZnSnO) channel with superior thickness uniformity and a p-type Si source. Careful optimization of the deposition condition of the ZnSnO layer leads to the significant improvement of the thickness uniformity thanks to its amorphous structure. It is promising to reduce the average sub-threshold swing (S.S.) of the bilayer TFET. The average S.S. of the amorphous ZnSn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The tunnel field-effect transistor (TFET) is one of the promising candidates for next-generation energy-saving devices, due to its much steeper on-off switching compared to conventional metal-oxide-semiconductor FETs. [1][2][3] Among various types of TFETs, [4][5][6][7][8][9][10][11][12][13][14][15] the Si-TFET is fascinating because it is fabricated based on the highly-developed Si technology. Owing to the indirect band-gap transitions, however, the tunneling ON current in Si-TFETs is low, compared to other TFETs made of III-V semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The tunnel field-effect transistor (TFET) is one of the promising candidates for next-generation energy-saving devices, due to its much steeper on-off switching compared to conventional metal-oxide-semiconductor FETs. [1][2][3] Among various types of TFETs, [4][5][6][7][8][9][10][11][12][13][14][15] the Si-TFET is fascinating because it is fabricated based on the highly-developed Si technology. Owing to the indirect band-gap transitions, however, the tunneling ON current in Si-TFETs is low, compared to other TFETs made of III-V semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the steep sub-threshold characteristics, the hysteresis-free characteristics of this W/Al 2 O 3 /ZnSnO/Si bilayer TFET are attractive for low-power switching devices. On the other hand, the SiO 2 interfacial layer formed at the ZnSnO/Si interface [20] may limit the I ON for all the TFETs, hence further process developments for suppressing the formation of the interfacial layers are expected to improve the TFET performances.…”
Section: Resultsmentioning
confidence: 99%
“…We have also experimentally demonstrated the TFET operation by utilizing ZnO/Si, ZnO/Ge [19], and ZnSnO/Si [20] bilayer TFET devices with a TiN/Al 2 O 3 gate stack, where it has been confirmed that the source-to-drain current is dominated by tunneling current [19]. However, the minimum SS values experimentally achieved so far have been 71 mV/dec.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…As for the OS materials, amorphous ZnSnO were studied. In order to further reduce the SS minimum, TiN/Al2O3(10nm), W/Al2O3(10nm) and W/HfO2(1nm)/Al2O3(9nm) gate stacks were employed for the ZnSnO channel with Zn/Sn ratio of 1.5 [16]. Fig.…”
Section: Materials and Gate Stack Optimizationmentioning
confidence: 99%